PERUBAHAN SOSIAL MASYARAKAT DI KAWASAN PENGEMBANGAN WISATA HUTAN PINUS MALINO KABUPATEN GOWA (Fakultas Dakwah dan Komunikasi, 2021)
This article discusses 1. How the existence of socio-cultural conditions of the community in the Malino pine forest development area of Gowa Regency, 2. Factors that influence the occurrence of social changes in the Malino pine forest development area of Gowa Regency and 3. How to form social changes that occur in the community in the Malino pine forest development area of Gowa Regency. The purpose of this research is 1. To find out the existence of socio-cultural conditions of the community in the Malino pine forest development area of Gowa Regency, 2. To find out the factors that affect the occurrence of social changes in the Malino pine forest development area of Gowa Regency. 3. To find out the form of social change that occurs in the community in the Malino pine forest development area of Gowa Regency. This research is qualitative research. Qualitative research methods are methods used to examine the natural conditions of objects. In this method of researchers use a sociological approach. The source of research data is primary and secondary data (Communities around Malino pine forest tourism). Furthermore, the data collection methods used are observations, interviews, documentation. Then, data management and analyst techniques are carried out through three stages, namely: data reduction, data presenter, and conclusion withdrawal. The results of this study show that the people around Malino pine forest tourism experience social changes well this can be seen from attitudes and behaviors. 1. Socio-cultural conditions of the community before and after the Malino pine forest tourist area, people's lives have developed from before 2. The existence of influencing factors, namely (factors of education, tourism, external culture / foreign economy and development in the region ) and 3. The form of social change that occurs is a. Changes in mindset (life has developed, thinking has advanced, and interaction with people/visitors increasingly open). b. A modern lifestyle and a growing language. The implication of this study is 1). Able to manage the conditions or opportunities that exist for the community 2). Various forms of business that can be built or run and 3). The author hopes that this study can provide understanding to readers and hopes that this research can be useful as a reference for readers in the future.